The control of constructive-technological parameters of the microstructured fibre in ACS of fibre drawing TP - Филипенко, Александр Иванович; Пономарева, Анна Викторовна (Eastern-European Journal of Enterprise Technologies, 2012)
Mathematical, informational and program supports of the automated control of constructive-technological parameters of the microstructured fiber during its drawing are developed.